Pengaruh PDRB, Jumlah Penduduk, Jumlah Angkatan Kerja Terhadap PAD - Sapira, Bella; Tiara, Shita (Forum Kerjasama Pendidikan Tinggi, 2022)
The starting point of this study is the increase and decrease in PDRB, population and labor force, but this phenomenon does not follow changes in regional primary income, so this is not in accordance with the theory of increasing regional primary income. PDRB will increase total PAD from the total population and labor force. This study aims to determine the effect of PDRB, population and labor force on the main regional income Regions/cities in North Sumatra. The type of quantitative research pursued in this study uses secondary data whose data comes from the North Sumatra Province data report for 2018-2022 published by the Central Bureau of Statistics. Sampling using targeted sampling.